Spatio-temporal niche plasticity of a freshwater invader as a harbinger of impact variability - Haubrock, Phillip J; Balzani, Paride; Matsuzaki, Shin-Ichiro S; Tarkan, Ali Serhan; Kourantidou, Melina; Haase, Peter (The Science of the total environment, 2021)
Invasive alien fishes have detrimental ecological effects on aquatic ecosystems and the services they provide. Impacts from an invasion in a single ecosystem may differ across space and time due to variability in prey availability and environmental conditions. We hypothesize that such variability can be profound, even within a single ecosystem. Stable isotopes analysis (SIA) is commonly used to quantitatively describe the trophic niche of a species. However, spatial and temporal variability in occupied niches are often not incorporated into management strategies and policy options. Here, we used long-term monitoring data to investigate the invasion stage as well as SIA to analyse the trophic niche of the invasive channel catfish Ictalurus punctatus in Lake Kasumigaura (Japan), a long-term ecological research site (LTER), across distant sampling sites and years. We found a significant spatio-temporal variability in relative growth and isotopic niche occupation. Moreover, we defined a new index, the Isotopic Plasticity Index (IPI), which is the ratio between core and total home range of an occupied isotopic niche, to be used as a proxy for the trophic niche stretch or density. We found that this IPI varied considerably, confirming the spatio-temporal variability in trophic niches, suggesting the IPI to be an adequate new isotopic metric. Our results further provide evidence for the existence of variation across invaded landscapes, implying heterogeneous impacts on recipient native communities. Therefore, our work emphasizes the importance of exploring trophic plasticity in feeding ecology and growth as such information enables a better understanding of impacts and can inform the design and implementation of effective management responses.
Keywords: Trophic ecology; Nitrogen Isotopes; Japan; Ecosystem; Lakes; izotopy dusíku; potravní řetězec; Long term monitoring; LTER; jezera; Food Chain; ryby; Invasive species; Fishes; Animals; zvířata; Japonsko; Plasticity; ekosystém; Spatio-temporal variability